Epidemiolgical characteristics of foodborne disease in Baiyun District of Guangzhou from 2018 to 2020 - LIN Hong; CHEN Liangfa; TAN Weixuan; LIANG Wenhui; LUO Guihe; PENG Huide; CAO Wenting (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo learn the epidemiological features of foodborne disease in Baiyun District， Guangzhou City from 2018 to 2020， so as to provide scientific basis for the development of targeted prevention and control measures.MethodsThe descriptive analysis method was used to analyze the data of 1 226 cases of foodborne diseases reported by surveillance hospitals in Baiyun District， Guangzhou City from 2018 to 2020. The epidemiological and clinical characteristics were described， and the Logistic regression analysis was conducted on the influencing factors of timely outpatient rate.ResultsFrom 2018 to 2020， there were 567 cases of foodborne diseases in males （46.25%， 567/1 226） and 659 cases in females （53.75%，659/1 226） in Baiyun District， Guangzhou City. The age of cases mainly ranged from 21 to 30 years old （37.19%，456/1 226）. The occupational distribution of cases was dominated by civil servants， employees of enterprises and institutions. The peak period was June to October. Family（41.80%， 754/1 804） was the main suspicious eating place. Meat and meat products were the main types of suspect foods. Catering service industry was the main processing and packaging method. Multivariate Logistic regression showed that old age， high hospital grade， vomiting times were positively correlated with the timeliness of health-seeking， diarrhea and diarrhea times were more negatively correlated.ConclusionThe high incidence of foodborne diseases in Baiyun District， Cuangzhou City was in hot seasons， and families and food service organizations were the high risk places. Food safety supervision and health education should be further targeted to prevent and control the occurrence and prevalence of food-borne diseases．